Assessment of the Landfill of the Thi-Qar Refinery and Propose the Alternative Landfill (Journal of University of Babylon for Engineering Sciences, 2018)
Oil sludge is one of the most significant wastes generated in the petroleum industry. A potentially contaminating waste product, with a high content of hydrocarbons and heavy metals. This study is to evaluate the effect of petroleum crude oil contaminated soil and groundwater using MODFLOW Flex software. Existing landfills are non-conforming to the environmental conditions.  Despite the fact that there are various techniques used for waste disposal, landfill is the most common mode for the disposal of waste in Iraq. landfill site selection criteria are quite complex process and it depends on several regulation and factors. In this study landfill site selection is performed using Geographic Information System (GIS) for (TOR). Existing landfills in (TOR) are non-conforming to the environmental conditions. In order to determine landfill site, several criteria were examined such as urban centers, land use, airports, pipes, power lines, railways, roads, slope, streams, surface water, industrial areas, oil pipes, liquid gas pipes, soil types are prepared. Each map layer was prepared using GIS and the final suitable map was created by overlay analyses of each criterion map. According to the results, a suitable landfill site was obtained in the study area.